The meaning of the term "the use of reason" in canon law - Dzierżon, Ginter (Prawo Kanoniczne, 2023)
In the presented study, the author attempted to define the normative meaning of the term "the use of reason". The conducted analyzes show that this term is not a psychological category, but a canonical one. Based on the assumptions of the normative legal theory, it was shown that it is not only an act of the intellect, but an intellectual-volitional act related to the subjective ability to take action. According to the author, it should generally be associated with human discernment, which should be proportional to the value of a specific act. The author showed that in systemic solutions, the judgement of an individual's condition depends on the discretion of a third party; the exception is the area of criminal law, where the legislator introduced a number of presumptions, both iuris et de iure and iuris tantum.